Sistem Informasi Manajemen Pengawasan Dan Pengendalian (WASDAL) Menara Telekomunikasi (Studi Kasus: Dinas Komunikasi Dan Informatika Kota Cimahi) - Mamay Syani; Yuda Pratama Jabir; Firdaus Laia; Eryan Ahmad Firdaus (NUANSA INFORMATIKA, 2024)
Telecommunication tower management information system is a crucial data processing system for telecommunication tower fee collection, given the importance of having an efficient and integrated system. However, the Department of Communication and Informatics of Cimahi City still lacks an integrated system, resulting in a slower telecommunication tower fee collection process. To address this issue, a Website named Telecommunication Tower Supervision and Control Management Information System (Wasdal) was developed as an integrated system to facilitate the fee collection process and generate fee collection reports. The methodology employed in this research is the Software Development Life Cycle (SDLC), and the Website is constructed using Laravel framework, Bootstrap, and MySQL database. The implementation results reveal that the overall built management information system Website meets user requirements. The User Acceptance Test (UAT) outcomes indicate average parameter scores of design (78%), features (79.20%), user satisfaction (80.60%), with an overall testing score of 81.3%.